(untitled) (Revista Sistemas de Producción Agroecológicos, 2018)
This experiment was carried out in a humid warm climate region with rainfall between 2700 and 3000 mm/year, with acid and low fertility soils, whose objective was to evaluate the application of calcium carbonate (CaCO3) and fertilizers in two types of grasses to establish interactions between soil chemical properties and forage production. The calculation of the amount of lime to be applied (total dose (TD)) was made based on the percentage of tolerable aluminum, for which the treatments were: E1 = 0 ton/ha (control), E2 = 0.74 ton/ha (1/3 of TD), E3 = 1.49 ton/ha (2/3 of TD) and E4 = 2.24 ton/ha (3/3 of TD) of CaCO3 applied in all treatments after the recovery of the pasture at 45 days. The design was randomized complete blocks with factorial arrangement by type of grass (Brachiaria decumbens and Brachiaria dictyoneura), applied dose of lime (4 amendments) and three components of fertilization (N, P, and K), with three repetitions for a total of 72 experimental units (2x4x3x3), each one of 16 m2, factors that were related to organic matter (OM), phosphorus (P), pH, aluminum (Al), calcium (Ca), magnesium (Mg), potassium (K) and sodium (Na). The variables analyzed were: green forage production (FV) and dry matter (DM). The statistical analysis was performed using ANOVA with 95% significance, and comparison of means with the Tukey test. The Al exchangeable in B. decumbens increased as the liming dose was increased, because in E3 and E4 it was greater than 2.2 cmolc/kg of soil; while with B. dictyoneura the dose of lime 1/3 of the total decreased it being less than 1.98, although both values remained high in the soil, indicating that the doses applied did not manage to reduce the excess of Al, being different from each other (P<0.05). B. decumbens showed higher production of FV and MS than B. dictyoneura (P<0.05), the difference between the production of fresh and dry biomass in both pasture species, was related with the own characteristics of the pastures and the tolerance of B. decumbens to the conditions of acidity and little influence of the limiting factors such as the excess of Al, low pH and content of OM and P. The highest dose of lime with urea in E3 improved the efficiency of the P available in the soil of the pastures, it also generated a higher biomass production under acid soil conditions. Potentializing the production factors of B. dictyoneura in the area would be important to improve its production, because with this species is increased the MO, the P available, and the exchangeable Al and pH are reduced; in comparison with B. decumbens, when is fertilized with N, the OM contents are improved; on the other hand, with all the liming doses evaluated, the exchangeable Al of the soil was reduced.